Analysis of Product Halal Aspects in Pak Juhari Sate Business, Nyurmanis Village, Blega SKB Sharia Perspective - Kholilur Rohman; Abdur Rohman (Penerbit Hellow Pustaka, 2024)
This study aims to gain a deep understanding of the various aspects relevant to the halal nature of food products produced by small and medium enterprises (SMEs). The research method employed is a literature study, involving the collection of data or information from various sources such as books, journals, and websites. The findings suggest that the analysis of business feasibility studies in the development of SMEs food products must ensure the halal status of the products. SMEs in the food sector must implement various production practices that meet the applicable halal standards. Based on the research, it can be concluded that in the context of SMEs business in the food sector. Product halalness is a very important factor in determining business feasibility and sustainability. External factors such as regulations, access to halal certification, and internal factors such as production management have a major influence on the business viability of SMEs. Strict regulations related to product halalness require SMEs to comply with set standards, wich can affect production costs and overall operational processes. This research hopes to provide recommendations that can help SMEs overcome challenges and enhance their business viability in producing halal and high-quality food products.